Pengaruh Debt To Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO) dan Net Profit Margin (NPM) Terhadap Pertumbuhan Laba Pada Perusahaan Pertambangan Batubara Yang Terdaftar Di BEI Tahun 2018-2022 - Fenty Febriani Yoldam Palayukan; Herman Karamoy; Robert Lambey (Universitas Sam Ratulangi, 2023)
Profit growth is an increase or decrease in the results of the company's profit from the previous year. Profit growth is uncertain, but can be predicted using financial ratio analysis. This study aims to determine the effect of DER, CR, TATO and NPM on profit growth in coal mining companies listed on the IDX in 2018-2022. The research method used is an associative quantitative method. The sampling technique in this study used non-probability sampling with a purposive sampling technique. The population in this study were 29 companies with 145 total financial report data and a sample of 9 companies with a total of 45 financial report data that met the criteria. The results of this study indicate that Debt To Equity Ratio (DER) and Net Profit Margin (NPM) have significant effect on profit growth, while Current Ratio (CR) and Total Asset Turnover (TATO) have no significant effect on profit growth in coal mining companies listed on the IDX in 2018-2022. Keywords: Debt to Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO), Net Profit Margin (NPM) and Profit Growth.